Mitral annular dysjunction in surgical mitral valve prolapse. (4th February 2022) - Gray, R; Cheuk-Lam, H; Turner, D; Mamo, A; Cranney, G; Mathur, R; Yu, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Mitral valve prolapse (MVP) affects 3% of the population and is the leading indication for mitral valve surgery.[1] Mitral annular disjunction (MAD) is a structural abnormality commonly seen in patients with MVP.[2] MAD is defined as an abnormal separation (>5mm) between the left atrial wall-mitral valve junction and the left ventricle myocardium, [2] associated with hypermobility and myxomatous degeneration of the mitral valve leaflets.[3]  There is a paucity of literature regarding MAD, however evidence is growing that it may be associated with ventricular arrhythmia and sudden cardiac death.[3] We examined the prevalence, imaging characteristics and clinical associations of MAD among patients who have undergone mitral valve surgery for MVP. Methods: Single centre cohort study of consecutive patients undergoing mitral valve surgery for MVP over a 3-year period. Patient baseline characteristics, echocardiographic parameters, surgical outcomes, frequency of arrhythmic events and 3-year cardiac and all-cause mortality were recorded.  Single site data was obtained from a prospective Australia-wide cardiac surgery registry, as well as retrospective analysis of holter-monitor reports, device interrogation and review of medical records. Transthoracic echocardiogram images were re-examined, and parameters re-measured by a qualified examiner. Results: Among 73 patients with surgical MVP, 20 patients had MAD (27.4%). The median MAD length was 8.1 (IQR 6.8-11.8) mm. The most severely affected patient had a disjunction length of 28 mm. MAD was associated with younger age at surgery (60 vs 66, P = 0.005), female sex (40.0% vs 22.6%, P = 0.138), bileaflet MVP (50% vs 10.6%, P = 0.004) and less cardiovascular comorbidities, including hypertension (25.0% vs 57.7%, P = 0.013) and hypercholesterolaemia (30.0% vs 61.5%, P = 0.016). Patients with MAD had greater mitral valve leaflet lengths, mitral annular diameters, and high-velocity systolic signal on tissue doppler of the mitral valve annulus (pickelhaube sign). Three patients in the MAD positive group had an arrhythmic event (VF or VT) at 3 years compared to one in the MAD negative group. There was no significant difference in 3-year cardiac or all-cause mortality between groups. Conclusion: MAD is a common anatomical abnormality in patients with surgical MVP, and is easily detected on transthoracic echocardiography. It is associated with younger age at surgery, female sex, bileaflet MVP, increased leaflet length and annulus diameter. There was a signal towards increased arrhythmic events in patients with MAD despite younger age and less cardiovascular risk factors. Large longitudinal studies are needed to further assess the association of MAD with arrhythmic events to help guild appropriate investigation and risk stratification of these patients.